MORAL AND DIDACTIC MAXIMS ABOUT FAMILY AND MARRIAGE: THE EXPERIENCE OF THEIR EVERYDAY EXISTENCE IN THE URBAN ENVIRONMENT OF ITALY IN XIV-XV CENTURIES - Irina Alekseevna Anuprienko (Гуманитарные и юридические исследования)
The article analises marriage trends during the XIV-XV-th centuries, as well as institutions of public order which con-trolled not only spiritual and emotional sphere, but also economic and political life of the family.